2014
DOI: 10.2215/cjn.01330214
|View full text |Cite
|
Sign up to set email alerts
|

Gene–Gene and Gene–Environment Interactions in Apolipoprotein L1 Gene-Associated Nephropathy

Abstract: Molecular genetics have revolutionized the understanding of susceptibility to the broad spectrum of kidney diseases with light microscopic appearance of FSGS, particularly in populations with recent African ancestry. These disorders include idiopathic FSGS, HIV-associated nephropathy, severe lupus nephritis, sickle cell nephropathy, and the primary kidney disorder focal global glomerulosclerosis, which had historically been ascribed to systemic hypertension. FSGS was once thought to include a multitude of unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 72 publications
1
89
0
Order By: Relevance
“…36 Having carried out our study in a high HIV prevalence setting, with predominantly HIV-1 subtype C, puts HIV as an important environmental factor inducing APOL1-mediated kidney disease, supporting a two-hit model for APOL1-associated disease expression. 37 This study highlights the need to consider gene-environment interaction in the interpretation of genome-wide association studies for other common diseases.…”
Section: Discussionmentioning
confidence: 94%
“…36 Having carried out our study in a high HIV prevalence setting, with predominantly HIV-1 subtype C, puts HIV as an important environmental factor inducing APOL1-mediated kidney disease, supporting a two-hit model for APOL1-associated disease expression. 37 This study highlights the need to consider gene-environment interaction in the interpretation of genome-wide association studies for other common diseases.…”
Section: Discussionmentioning
confidence: 94%
“…Additional genetic and/or nongenetic factors seem to modify the risk of kidney disease progression in individuals with the high-risk APOL1 genotype (8). One such example is HIVAN.…”
Section: Introductionmentioning
confidence: 99%
“…Although individuals with two APOL1 high-risk alleles have a 4.25% lifetime risk of developing FSGS, those additionally infected with HIV have a 50% lifetime risk of developing HIVAN (6). Moreover, control of HIV infection with highly active antiretroviral therapy reduces the risk of CKD in patients with the APOL1 high-risk genotype (8)(9)(10). In another example, Divers et al (11) reported that the presence of JC viruria may be protective against kidney disease among individuals with two APOL1 high-risk alleles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The APOL1 high-risk genotype (two copies of the G1 or G2 alleles) has a population frequency of approximately 13% in African Americans and confers an approximately 2-fold higher risk for kidney function decline in cohort studies (8,9). Although the role of APOL1 in relation to kidney function is largely unknown, environmental factors probably affect APOL1-associated renal risk (10). For example, HIV infection (and particularly an unsuppressed viral load) in individuals with the APOL1 high-risk genotype appears to increase the susceptibility for progressive kidney disease (11,12).…”
Section: Introductionmentioning
confidence: 99%